Determinan Perilaku Food waste Mahasiswa Fakultas Pertanian Universitas Jember - Nathania Kristin Zalukhu; Feni Novia Agustin; Muhammad Helmi Setiawan (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2026)
Food waste represents a significant global and national challenge with major economic impacts. While students at the Faculty of Agriculture, University of Jember, have a solid understanding of the food system, their actual consumption habits warrant closer investigation. This study explores the factors shaping food waste behavior among these students through the Theory of Planned Behavior (TPB). A quantitative method was employed, involving questionnaires completed by 55 active students. The data analysis utilized the Structural Equation Modeling - Partial Least Squares (SEM-PLS) technique. Overall, findings show that attitude does not significantly affect students' food waste behavior, whereas subjective norms and perceived behavioral control do. Notably, perceived behavioral control emerges as the most critical factor in minimizing food wastage among students.